Determination of Appropriate Time of Nitrogen Fertilizer Application for Maize in the Central Highlands of Ethiopia - Mamo, Midekesa Chala; Chala Chalchissa, Chala; Biratu, Gudeta (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Excessive nitrogen fertilization and improper management can cause a decrease in NUE in the maize cropping system. Most nitrogen fertilizers are applied when the corn is 4-5 weeks after planting. However, recent studies have shown that modern hybrids take up high amounts of nitrogen at the flowering stage. This suggests that a nitrogen fertilization strategy that starts at the beginning of vegetative growth and later in the flowering phase is needed to maximize the yield of hybrid maize in upland. The study was conducted in 2018-2019 in Liban, Jawi, and Toke Kutaye Districts in the West Showa Zone of the Central Highlands of Ethiopia. The research design used a randomized block design with the one-time treatment of fertilizer application consisting of six levels, namely 1/3 at planting + 1/3 at 4-5 weeks after an emergency (WAE) + 1/3 at 70-80 days after planting (DAP ); 1/3 part at planting + 2/3 part at 4-5 WAE; 2/3 share at 4-5 WAE + 1/3 at 70-80 DAP; 1/4 at planting + 1/2 at 4-5 WAE + 1/4 at 70-80 DAP; 1/2 at 4-5 WAE + 1/2 at 70-80 DAP; and full at 4-5 WAE). Nitrogen fertilization on2/3part at 4-5 WAE + 1/3 part at 70-80 DAP significantly affected plant height, cob length, grain yield, and biomass yield, but it did not influence root and stem lodging. When the data were combined over the two years, the treatment of 2/3part N application at 4-5 WAE (knee height) + 1/3 part at 70-80 DAP (before tasseling) resulted in the highest grain yield with a yield advantage of 1,598 kg/ha and gave maximum net benefit over the typically used full application at 4-5 WAE (knee height). This fertilizer management strategy could be advised for the Liban Jawi, Toke Kutaye areas, and other similar agro-ecosystem environments.